Design Planning of Wastewater Treatment Plant at Lading Hotel Banda Aceh - Dian Fatziaty; Vera Viena; Teuku Muhammad Ashari (Universitas Serambi Mekkah, 2024)
Lading Hotel is one of the hotel industries that has a strategic location in the city center of Banda Aceh. Lading Hotel produces domestic wastewater as much as 95,000 L / day generated from kitchen activities, laundry, bathrooms, and cafes. The wastewater preliminary results showed the parameter COD 381 mg / L and TSS 371 mg / L has exceeded the quality standards set by the government. To addresses these problems, this study aims to do a design planning of the wastewater treatment plant (WWTP) in Hotel Lading. The steps of treatment technology chosen in this study consist of equalization basins, sedimentation basins with additional aeration from blowers, anaerobic biofilter basins and subsurface flow type wetlands. The planning stages include collecting data, processing data, design planning, making BoQ and drawing conclusions. The results of dimensions calculation for design drawings e.i: the equalization basin is 3.6 m × 2 m × 3 m (7.4 m2), sedimentation basin with dimensions of 3.6 m × 1.8 m × 3 m (6.48 m2), anaerobic biofilter basin with dimensions of 2.4 m × 1.2 m × 3 m (2.88 m2) and Subsurface wetland dimensions of 4 m × 1 m × 1 m (4 m2). Total land area required for WWTP design planning was 20.76 m2.